Quality Analysis of a Mobile Attendance Application Using ISO/IEC 25010 and User Satisfaction Measurement - Dimas Ardhana; Deva Rahma Aulia (Journal Innovation in Information and Computer Technology, 2025)
The increasing use of mobile technology has encouraged many institutions and organizations to adopt mobile attendance applications as a practical solution for recording attendance activities. However, the success of such applications depends not only on their technical functionality but also on user satisfaction. This study aims to analyze the quality of a mobile attendance application using selected dimensions of ISO/IEC 25010 and user satisfaction measurement. The research employed a quantitative descriptive method by collecting data through questionnaires and direct observation. The evaluated dimensions included Functional Suitability, Performance Efficiency, Usability, Reliability, Security, and Portability, followed by overall user satisfaction assessment. The results showed that the application achieved an average score of 82.1%, categorized as Very Good. Functional Suitability obtained the highest score, indicating that the application features effectively support attendance activities. Meanwhile, Performance Efficiency and Reliability received relatively lower scores, suggesting the need for further improvement in system speed and stability. User satisfaction was also rated highly, demonstrating positive acceptance of the application among users. The findings confirm that combining ISO/IEC 25010 with user satisfaction measurement provides a comprehensive evaluation approach that captures both technical quality and user experience. This study may serve as a reference for developers and institutions in improving the effectiveness and acceptance of mobile attendance systems.